Workplace infection control measures and romantic activities of workers during COVID-19 pandemic: A prospective cohort study in Japan - Fujino, Yoshihisa; Okawara, Makoto; Hino, Ayako; Muramatsu, Keiji; Nagata, Tomohisa; Ikegami, Kazunori; Tateishi, Seiichiro; Tsuji, Mayumi; Ishimaru, Tomohiro (Frontiers in Public Health, 2023)
Objective: Due to the COVID-19 pandemic, non-married people are at high risk of loneliness. With social interactions restricted, it is important for non-married people to acquire a new romantic partner for their mental health and quality of life. We hypothesized that infection control efforts in the workplace influence people’s social interactions, including romantic activities. Methods: We conducted an internet-based prospective cohort study from December 2020 (baseline) to December 2021, using self-administered questionnaires. Briefly, 27,036 workers completed the questionnaires at baseline, and when followed up after one year, 18,560 (68.7%) participated. A total of 6,486 non-married individuals with no romantic relationship at baseline were included in the analysis. At baseline they were asked about the implementation of infection control measures in the workplace, and at follow-up they were asked about activities they performed with a view to romantic relationships during the period from baseline to follow-up. Results: Compared to workers in workplaces with no infection control measures, the OR associated with romance-related activities for those in workplaces with seven or more infection control measures was 1.90 (95% CI: 1.45-2.48, p<0.001), and the OR associated with having a new romantic partner was 1.79 (95% CI: 1.20-2.66, p=0.004). Discussion: Under the COVID-19 pandemic, the implementation of infection control measures in the workplace and the expressed satisfaction with those measures promoted romantic relationships among non-married, single individuals.